Political philosophy (Society for the Diffusion of Useful Knowledge, 1798)
Vol. 1. Principles of government; Monarchical government; Eastern monarchies; European monarchies. Vol. 2. Of Aristocracy; Aristocratic governments. Vol. 3. Of democracy; Mixed monarchy.